Studi Kapasitas Leksikon Mental pada Subjek Berjenis Kelamin Laki-Laki dan Perempuan Melalui Alat Uji Asosiasi Kata: Suatu Kajian Psikolinguistik - Avinda Elsa Febriani; Raihanah Nasywa; Siti Halimah; Fatmawati Fatmawati; Rhani Febria (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The human brain's repository for all vocabulary and its representations is called the mental lexicon. The meaning and conceptualization of an individual or group are what connect brain words to one another. Men's and women's mental lexicons will be examined in this study to determine whether there are differences or similarities. A word association test tool was used by the researchers to support this study. This study used a word association test to examine the mental lexicons of male and female subjects from the two age categories. Descriptive qualitative research is used in this study. On the basis of the data analysis that has been described, it was determined that male and female subjects' mental lexicon capacities were significantly different. Female participants have a significantly higher mental lexicon capacity than male participants. Female participants exhibit decreased performance in the context of individual issues that have a negative emotional impact, whereas male participants exhibit an upward performance curve in each interview session without exhibiting emotional changes. This supports Tyng, Amin, Saad, & Malik's (2017) theory that emotions have a significant impact on thought processes, particularly those related to perception, attention, learning, memory, logic, and problem-solving.